Oscillation of solutions of second order nonlinear functional differential equations of neutral type - Ivanov, A.F.; Kusano, T. (Український математичний журнал, 1991)
The oscillation condition of solutions to nonlinear differential equations of the second order of neutral type on the semiaxis t > 0 and the properties of nonoscillatory solutions are investigated. Исследованы условия осцилляции решений нелинейных дифференциальных уравнений второго порядка нейтрального типа на полуоси t > 0, а также свойства неосциллирующих решений.